Kepemimpinan Demokratis KH. Salahuddin Wahid Dalam Meningkatkan Pendidikan Islam Modern Di Pesantren Tebuireng - Saefrudin, Saefrudin (Rayah Al-Islam, 2025)
K.H. Salahuddin Wahid is a national figure with a background in architectural education, he is called a technocrat because of his role in physical development at Pesantren Tebuireng Jombang. The purpose of this study was to analyze KH. Salahudin Wahid's democratic leadership in Improving Modern Islamic Education at Pesantren Tebuireng. Using a qualitative approach with a historical method, data was collected through interviews, observation, and document analysis.  The results of this study show that KH Salahudin Wahid's profile shows good democratic leadership characteristics, including moderate influence, inspirational motivation, intellectual, and collective consideration. His leadership strategy of integrating Islamic and general education of Pesantren Tebuireng has undergone changes in the era of the caretaker of K.H. Salahuddin Wahid. Through his role, Pesantren Tebuireng experienced changes in physical and non-physical aspects and the construction of new buildings to support facilities. In the non-physical field, K.H. Salahuddin Wahid established many units to support the process of organizing the pesantren. The impact is significant, improving the quality of education, modernizing physical facilities, strengthening the role of pesantren in society, and expanding the alumni network.